Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1)
Ta có: \(8⋮x\)
\(\Rightarrow x\inƯ\left(8\right)\)
\(\Rightarrow x\in\left\{\pm1;\pm2;\pm4;\pm8\right\}\)
mà x>0 nên \(x\in\left\{1;2;4;8\right\}\)
Vậy: \(x\in\left\{1;2;4;8\right\}\)
2)
Ta có: \(12⋮x\)
\(\Rightarrow x\inƯ\left(12\right)\)
\(\Rightarrow x\in\left\{\pm1;\pm2;\pm3;\pm4;\pm6;\pm12\right\}\)
mà x<0 nên \(x\in\left\{-1;-2;-3;-4;-6;-12\right\}\)
Vậy: \(x\in\left\{-1;-2;-3;-4;-6;-12\right\}\)
3)
Ta có: \(-8⋮x\) và \(12⋮x\)
nên \(x\inƯC\left(-8;12\right)\)
mà \(Ư\left(-8\right)=\left\{\pm1;\pm2;\pm4;\pm8\right\}\)
và \(Ư\left(12\right)=\left\{\pm1;\pm2;\pm3;\pm4;\pm6;\pm12\right\}\)
nên \(x\in\left\{1;-1;2;-2;4;-4\right\}\)
Vậy: \(x\in\left\{1;-1;2;-2;4;-4\right\}\)
a) \(\left(2x+10\right)\left(x^2-9\right)=0\)
\(\Leftrightarrow\)\(2\left(x+5\right)\left(x^2-3x+3x-9\right)=0\)
\(\Leftrightarrow\)\(2\left(x+5\right)\left(x-3\right)\left(x+3\right)=0\)
\(\Leftrightarrow\)\(x+5=0\) \(\Leftrightarrow\)\(x=-5\)
hoặc \(x-3=0\) hoặc \(x=3\)
hoặc \(x+3=0\) hoặc \(x=-3\)
Vậy....
(x+3)(x-2)<0
=>x+3>0 và x-2<0
=>-3<x<2
=>\(x\in\left\{-2;-1;0;1\right\}\)
a) \(x=\dfrac{1}{4}+\dfrac{2}{13}\)
\(x=\dfrac{13}{52}+\dfrac{8}{52}\)
⇒ \(x=\dfrac{21}{52}\)
b) \(\dfrac{x}{3}=\dfrac{2}{3}+\dfrac{-1}{7}\)
\(\dfrac{x}{3}=\dfrac{14}{21}+\dfrac{-3}{21}\)
\(\dfrac{x}{3}=\dfrac{11}{21}\)
⇒ \(x=\dfrac{11.3}{21}=\dfrac{33}{21}\)
⇒ \(x=\dfrac{11}{7}\)
c) \(\dfrac{-8}{3}+\dfrac{1}{3}< x< \dfrac{-2}{7}+\dfrac{-5}{7}\)
\(\dfrac{-17}{7}< x< -1\)
⇒ \(-17< x< -7\)
⇒ \(x\in\left\{-16;-15,....;-6\right\}\)
d) \(\dfrac{1}{6}+\dfrac{2}{5}\)
\(=\dfrac{5}{30}+\dfrac{12}{30}\)
\(=\dfrac{17}{30}\)
e) \(\dfrac{3}{5}+\dfrac{-7}{4}\)
\(=\dfrac{12}{20}+\dfrac{-35}{20}\)
\(=\dfrac{-23}{20}\)
f) \(\dfrac{4}{13}+\dfrac{-12}{30}\)
\(=\dfrac{4}{13}+\dfrac{-2}{5}\)
\(=\dfrac{20}{65}+\dfrac{-26}{65}\)
\(=\dfrac{-6}{65}\)
g) \(\dfrac{-3}{29}+\dfrac{16}{58}\)
\(=\dfrac{-6}{58}+\dfrac{16}{58}\)
\(=\dfrac{10}{58}\)
h) \(\dfrac{8}{40}+\dfrac{-36}{45}\)
\(=\dfrac{1}{5}+\dfrac{-4}{5}\)
\(=\dfrac{-3}{5}\)
j) \(\dfrac{-8}{18}+\dfrac{15}{27}\)
\(=\dfrac{-2}{9}+\dfrac{5}{9}\)
\(=\dfrac{3}{9}\)
\(=\dfrac{1}{3}\)